ChemInform Abstract: A Novel, Green 1‐Glycyl‐3‐methyl Imidazolium Chloride—Copper(II) Complex Catalyzed C—H Oxidation of Alkyl Benzene and Cyclohexane. Issue 5 (13th February 2013) - Karthikeyan, Parasuraman; Bhagat, Pundlik Rambhau; Kumar, S. Senthil
Abstract The catalyst can be reused 7 times without significant loss of activity.